The Importance of Motivation to Older Adult Physical and Cognitive Exercise Program Development, Initiation, and Adherence - O’Neil-Pirozzi, Therese M.; Cattaneo, Gabriele; Solana-Sánchez, Javier; Gomes-Osman, Joyce; Pascual-Leone, Alvaro (Frontiers in Aging, 2022)
Brain health is essential to successful aging, and exercise is essential to brain health. Evidence supports the benefits of regular physical and cognitive exercise in preventing or delaying progression of mild cognitive impairment and dementia. Despite known benefits, motivation to initiate and adhere to an exercise program can be challenging to older adults. We propose that assessment of motivation in the older adult population be part of individualized physical and cognitive exercise program initial development and ongoing precision health coaching to facilitate initiation of – and adherence to – individualized multi-modal exercise programs and sustained exercise engagement. We suggest one published, physical exercise motivation questionnaire and present a new, psychometrically supported, parallel cognitive exercise questionnaire to do so. Needs for – and implications of – continued exercise motivation research using neurophysiologic and neuropsychologic metrics are discussed.